2022
DOI: 10.3390/membranes12100945
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Carotenoids Modulate the Thermotropic Phase Behavior of Model Systems That Mimic Its Membrane Composition

Abstract: Staphylococcus aureus (S. aureus) is a pathogenic gram-positive bacterium that normally resides in the skin and nose of the human body. It is subject to fluctuations in environmental conditions that may affect the integrity of the membrane. S. aureus produces carotenoids, which act as antioxidants. However, these carotenoids have also been implicated in modulating the biophysical properties of the membrane. Here, we investigate how carotenoids modulate the thermotropic phase behavior of model systems that mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In addition, these compounds were reported to engage in photoprotection, and membrane stabilization [ 56 , 57 , 58 ]. Certain studies report that carotenoids possibly lowered the phase transition temperature of synthetic lipids and worked as regulators for membrane fluidity since they showed an important role in the causative function in the modulation of membrane parameters [ 59 , 60 ]. It was found that carotenoids increased membrane order with concurrent maintenance of lateral lipid motility, which resulted in a liquid-ordered membrane state [ 61 ] The increase in membrane order was indicated to be related to a simultaneous increase in membrane fluidity, and an increase in the concentration of carotenoids led to an increase in the resistance of the cell against freeze-thaw stress [ 54 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…In addition, these compounds were reported to engage in photoprotection, and membrane stabilization [ 56 , 57 , 58 ]. Certain studies report that carotenoids possibly lowered the phase transition temperature of synthetic lipids and worked as regulators for membrane fluidity since they showed an important role in the causative function in the modulation of membrane parameters [ 59 , 60 ]. It was found that carotenoids increased membrane order with concurrent maintenance of lateral lipid motility, which resulted in a liquid-ordered membrane state [ 61 ] The increase in membrane order was indicated to be related to a simultaneous increase in membrane fluidity, and an increase in the concentration of carotenoids led to an increase in the resistance of the cell against freeze-thaw stress [ 54 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…The physical aspects that were explored were lipid headgroup spacing as measured with Laurdan fluorescence GP, mobility in the membrane core as measured with DPH fluorescence anisotropy, and lipid acyl chain order as measured with FTIR spectroscopy. Thermotropic measurements were performed in order to observe the behavior of the membrane in the gel phase regime at low temperatures and the liquid-crystalline regime at high temperatures, and also to assess gel to liquid-crystalline phase transition temperatures, which are important indicators of the membrane physical state [6,8,10,11]. Downward shifts in the phase transition temperature indicate that the liquid-crystalline phase of the membrane is stabilized with respect to the gel phase.…”
Section: Variation In the Biophysical Properties Of S Aureus Membranesmentioning
confidence: 99%
“…This result is important due to the fact that the more disordered liquid-crystalline phase is considered the physiologically relevant phase due to its increased mobility. By making the gel phase more disordered, carotenoid production may help the bacteria maintain a physiologically active membrane at low temperatures [8,10]. A recent study by Seel et al showed that carotenoids regulate membrane fluidity in Staphylococcus xylosus, in particular greatly affecting the fluidity of the membrane at low temperatures [32].…”
Section: Variation In the Biophysical Properties Of S Aureus Membranesmentioning
confidence: 99%
See 2 more Smart Citations